Home Alone: Is This the Best We Can Do? A Proposal to Amend Pending Parental Leave Legislation - Caldwell G. Collins (Washington University Journal of Law & Policy, 2009)
Part I of this Note examines the history of parental leave in America. Part II analyzes that history to assess its ineffectiveness in achieving the goal of gender equality in the workplace. Part III proposes a solution to the problem of gendered patterns of care as reinforced by our current system of parental leave.
Keywords: Parental leave; Employment discrimination; Gender equality; Maternity and paternity leaves; Sex discrimination